Role of Topical Cyclosporin in Scleritis: A Case Series - Harris Iqbal, Sameera Irfan (Pakistan Journal of Ophthalmology, 2018)
Purpose: To report on a series of cases of anterior, non-necrotizing scleritis, that were effectively treated with topical 0.075% - 1% cyclosporine A and to provide a literature review on other treatment modalities of this condition. Material and Methods: This study includes eleven consecutive patients of acute anterior, non-necrotizing scleritis reporting to Mughal eye hospital, Lahore, during January to December 2012. There were 7 females and 4 males between the age 18 and 65 years. They all had mild to moderate, anterior scleritis, nodular in 6 cases and diffuse in 5 cases. All patients were thoroughly investigated regarding auto-immune disorders. Only 2 cases had associated rheumatoid arthritis. They were treated with topical cyclosporine and preservative-free artificial tears for 2-3 months and followed-up for 1 year regarding recurrence. Results: All patients showed a favorable response to treatment. The scleritis score improved remarkably within 2 weeks of Cyclosporin therapy. The symptoms flared up in only 2 out of 11 cases (18%) when they abruptly stopped therapy. All cases remained asymptomatic over the one year follow-up after stopping treatment. Conclusion: Topical 0.075% - 1% Cyclosporine A is a safe and effective longterm treatment of anterior scleritis of mild to moderate severity. It should be considered as a steroid-sparing agent, particularly in recurrent disease and in those patients who experience adverse effects of systemic medications.